Prediabetes and serum insulin levels - Altemani, Alwaleed; Alamri, Ali; Ahmed, Mahir; Al Garbo, Mosaed; Alharbi, Tariq; Al-Rasheed, Rana; Alshagraawi, Saud; Alzilai, Ibrahim; Alotaibi, Fuad; Al-shahrani, Ahlam (International Journal Of Community Medicine And Public Health, 2018)
Prediabetes remains a diagnostic dilemma. It refers to impaired glycaemic values without reaching the threshold for diagnosing diabetes mellitus. Prediabetes is an important risk factor for the development of diabetes mellitus, and it constitutes the stage during which microvascular and macrovascular complications are initiated. Early and accurate identification of this stage is the gold standard for prevention of diabetes and its consequences. Despite the multiplicity of diagnostic tests proposed for identification of this condition, a reliable test remains elusive. This article aims at reviewing the different available tests for diagnosis of prediabetes states with a focus on serum insulin levels. Insulin plays a major role in the pathophysiology and development of prediabetes. Different mechanisms of insulin resistance and insulin secretion are established in different subtypes of prediabetes. Therefore, fasting insulin level seems to be a reliable and promising tool for diagnosis and management of prediabetes.